Human Trafficking In Accordance with Prosperity and National Economic Development - Renny Supriyatni Bachro; Mien Rukmini (Jurnal Cita Hukum, 2018)
Abstract:Nowadays, Human trafficking has spread their wings and becomes a crime, the trafficker works with a good organization and works between country to country, it becomes a threat for society, nation and country itself. To prevent this issue, we need to collaborate with another institutions. Law enforcer, government, Social services and also Non-Governmental Organization need to collaborate to resolve this issue for Indonesia and for International society. Government has a responsibility and also active in various development condition such as prosperity development, economic development because it is the main responsibility for country to protect the law of the country including Human rights. This main responsibility cannot be reduced by political reasons, economic and also cultural reasons. This research aims an overview of the solutions regarding the form of the prevention and the protection of the law against human trafficking and also to find a concrete measure in the form of regulations to covers the victims of the human trafficking for a prosperity and economic development. However, based on the empirical data, there are many problems and obstacles in the implementation of the provision of legal protections in the term of restitution and rehabilitation. The suggestion is, to prevent and to protect human trafficking victims, we need to make sure the local regulations in each province is suitable with the act of PTPPO and also, we need to strengthen the coordination. Moreover, to strengthen the prosperity of the human trafficking victims and to immune the economic development in society, we need to make sure the coordination between the central government and the local government in each province is strong in the term of budgeting. The utilizations of the APBN is to covers about prosperity and local economic development in the village who have the most potential to be a human trafficking victim.Keyword: Human Trafficking, Protections of the victims, prevention, Welfare and economics.Abstrak: Saat ini, perdagangan manusia telah melebarkan sayap dan menjadi kejahatan. Pelaku bekerja dengan organisasi yang baik dan memiliki jaringan antar negara. Ia menjadi ancaman bagi masyarakat, bangsa dan negara itu sendiri. Untuk mencegah masalah ini, perlu dilakukan kolaborasi dengan institusi lain. Penegak hukum, pemerintah, layanan sosial dan juga LSM (organisasi non-pemerintah) perlu berkolaborasi untuk menyelesaikan masalah ini bagi Indonesia dan masyarakat internasional. Pemerintah pun memiliki tanggung jawab dan juga aktif dalam berbagai kondisi pembangunan seperti pembangunan kemakmuran, pembangunan ekonomi karena merupakan tanggung jawab utama bagi negara untuk melindungi hukum negara termasuk hak asasi manusia. Penelitian ini bertujuan untuk memberikan gambaran tentang solusi mengenai bentuk pencegahan dan perlindungan hukum terhadap perdagangan manusia dan juga untuk menemukan langkah-langkah konkret dalam bentuk peraturan yang mencakup korban perdagangan manusia untuk kemakmuran dan pembangunan ekonomi. Namun, berdasarkan data empiris, ada banyak masalah dan hambatan dalam pelaksanaan ketentuan perlindungan hukum dalam istilah restitusi dan rehabilitasi. Karenanya untuk mencegah dan melindungi korban perdagangan manusia, perlu dipastikan bahwa peraturan lokal di setiap provinsi sesuai dengan tindakan PTPPO dan juga perlu memperkuat koordinasi. Selain itu, untuk memperkuat kemakmuran korban perdagangan manusia dan untuk melindungi perkembangan ekonomi masyarakat, perlu juga dipastikan koordinasi antara pemerintah pusat dan pemerintah daerah di setiap provinsi khususnya dalam hal penganggaran. APBN pun juga harus mencakup kemakmuran dan pembangunan ekonomi lokal di desa, karena desa paling berpotensi menjadi korban perdagangan manusia.Kata Kunci: Human Trafficking, Perlindungan Korban, Kesejahteraan dan EkonomiDOI: 10.15408/jch.v6i1.8265